Surface Connectivity and Interocean Exchanges From Drifter‐Based Transition Matrices. Issue 1 (19th January 2018) - McAdam, Ronan; van Sebille, Erik
Abstract: Global surface transport in the ocean can be represented by using the observed trajectories of drifters to calculate probability distribution functions. The oceanographic applications of the Markov Chain approach to modeling include tracking of floating debris and water masses, globally and on yearly‐to‐centennial time scales. Here we analyze the error inherent with mapping trajectories onto a grid and the consequences for ocean transport modeling and detection of accumulation structures. A sensitivity analysis of Markov Chain parameters is performed in an idealized Stommel gyre and western boundary current as well as with observed ocean drifters, complementing previous studies on widespread floating debris accumulation. Focusing on two key areas of interocean exchange—the Agulhas system and the North Atlantic intergyre transport barrier—we assess the capacity of the Markov Chain methodology to detect surface connectivity and dynamic transport barriers. Finally, we extend the methodology's functionality to separate the geostrophic and nongeostrophic contributions to interocean exchange in these key regions. Key Points: The error within probabilistic ocean surface transport models is highlighted Fluxes at key interocean exchanges are recreated within the model The role of geostrophic flow in interocean connectivity is explored